Implementation of team-based learning on a large scale : three factors to keep in mind* - Rajalingam, Preman (2018)
Team-based learning (TBL) is a structured form of small group learning that can be scaled up for delivery in large classes. The principles of successful TBL implementation are well established. TBL has become widely practiced in medical schools, but its use is typically limited to certain courses or parts of courses. Implementing TBL on a large scale, across different courses and disciplines, is the next logical step. The Lee Kong Chian School of Medicine (LKCMedicine), a partnership between Nanyang Technological University, Singapore and Imperial College London, admitted its first students in 2013. This new undergraduate medical program, developed collaboratively by faculty at both institutions, uses TBL as its main learning and teaching strategy, replacing all face-to-face lectures. TBL accounts for over 60% of the curriculum in the first two years, and there is continued learning through TBL during campus teaching in the remaining years. This paper describes our experience of rolling out TBL across all years of the medical curriculum, focusing on three success factors: (1) “team-centric” learning spaces, to foster active, collaborative learning; (2) an e-learning ecosystem, seamlessly integrated to support all phases of the TBL process and (3) teaching teams in which experts in pedagogical process (TBL Facilitators) co-teach with experts in subject matter (Content Experts).